Perbandingan Kemampuan Berpikir Analitis Model Pembelajaran MEA dan RTE dengan Memperhatikan AQ - Defika Putri Nastiti; Edy Purnomo; Pujiati Pujiati (JEE (Jurnal Edukasi Ekobis), 2017)
The purpose of this research is to know the difference of thinking ability of student analysis which learning using cooperative model type Means-Ends Analysis and Rotating Trio Exchange, and interaction to learning model by considering adversity quotient. The method research used is quasi experiment with comparative approach design by level. The population in this study is as many as 4 classes with the number of 170 students and the sample used as much as 2 classes with the number of 88 students determined through cluster random sampling. Data collection techniques through tests and questionnaires. Hypothesis testing used two way street variance analysis and two independent sample t-test. Based on the data analysis, the results obtained are: There is a difference of analytical thinking ability among students whose learning using Means-Ends Analysis learning model with Rotating Trio Exchange learning model on economic subjects, and There is an interaction between the use of learning models with adversity intelligence to the ability of analytical thinking.Tujuan penelitian ini untuk mengetahui perbedaan kemampuan berpikir analitis antara siswa yang pembelajarannya menggunakan model kooperatif tipe Means-Ends Analysis dan Rotating Trio Exchange, serta interaksi antara model pembelajaran terhadap kecerdasan adversitas. Metode penelitian yang digunakan adalah eksperimen semu dengan pendekatan komparatif desain by level. Populasi dalam penelitian ini sebanyak 4 kelas dengan jumlah 170 siswa dan sampel yang digunakan sebanyak 2 kelas dengan jumlah 88 siswa yang ditentukan melalui cluster random sampling. Teknik pengumpulan data melalui tes dan angket. Pengujian hipotesis menggunakan analisis varians dua jalan dan t-tes dua sampel independen. Berdasarkan analisis data diperoleh hasil: Ada perbedaan kemampuan berpikir analitis antara siswa yang pembelajarannya menggunakan model Means-Ends Analysis dengan model Rotating Trio Exchange pada mata pelajaran ekonomi, dan Ada interaksi antara penggunaan model pembelajaran dengan kecerdasan adversitas terhadap kemampuan berpikir analitis.Kata kunci: analisis, kecerdasan adversitas, mea, rte